2015
DOI: 10.1007/s00592-015-0822-0
|View full text |Cite
|
Sign up to set email alerts
|

Smoking and progression of diabetic nephropathy in patients with type 1 diabetes

Abstract: Current smoking is a risk factor for the progression of diabetic nephropathy and the risk increases with the increasing dose of smoking. Ex-smokers seem to carry a similar risk of progression of diabetic nephropathy as nonsmokers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
37
0
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 52 publications
(39 citation statements)
references
References 32 publications
1
37
0
1
Order By: Relevance
“…Indeed, we found that the association between RI and serum phosphate is independent from renal function. With respect to smoking habit, several prospective studies have demonstrated that cigarette smoking is strictly associated with a higher CKD progression rate in different clinical conditions, such as diabetic nephropathy, IgA nephropathy and membranous idiopathic nephropathy [50][51][52]. Various mechanisms have been indicated to explain the nephrotoxic effect of smoking.…”
Section: Plos Onementioning
confidence: 99%
“…Indeed, we found that the association between RI and serum phosphate is independent from renal function. With respect to smoking habit, several prospective studies have demonstrated that cigarette smoking is strictly associated with a higher CKD progression rate in different clinical conditions, such as diabetic nephropathy, IgA nephropathy and membranous idiopathic nephropathy [50][51][52]. Various mechanisms have been indicated to explain the nephrotoxic effect of smoking.…”
Section: Plos Onementioning
confidence: 99%
“…A recent study of 3613 T1DM patients showed that the 12-year cumulative risks of microalbuminuria, overt proteinuria and ESRD were significantly higher in current and ex-smokers compared to non-smokers and the risk increases with increasing the dose of smoking [63]. Quitting smoking is mandatory not only in T1DM but also in T2DM.…”
Section: Methodsmentioning
confidence: 99%
“…The risk of the progression of renal disease in ex-smokers compared to never-smokers is similar, thus all patients with diabetes who smoke should be advised to stop. 12 High protein and high salt intake should be avoided. 13 Physical activity, and weight loss in the overweight or obese, is associated with a positive effect on risk and progression of diabetic nephropathy.…”
Section: Lifestyle Modificationmentioning
confidence: 99%